Análisis del desempeño sísmico del edificio de aulas de la unidad académica de ingeniería civil - Mancheno Torres, Stefany Judith (2017)
The continuous seismic activity in the country makes it necessary to promote the construction of ductile structures, capable of deforming in the inelastic range without collapse, seeking to safeguard the lives of its occupants, as well as making it necessary for current structures to be analyzed to verify their performance against the action of earthquakes. In order to verify the current state of the building of classrooms of the Academic Unit of Civil Engineering of the Technical University of Machala, and its behavior against the probable action of an earthquake on it, the present work is carried out, which based on analyzing the seismic response of the structure under the guidelines indicated in the Ecuadorian Construction Standard 2015 (NEC-15). Initially, the theoretical basis governing the investigation of the seismic behavior of concrete buildings, the seismic hazard of a locality and the seismic vulnerability of buildings are presented, as well as the data from the Ecuadorian Construction Standard NEC-15 for the analysis of structures. Considering that it is a building with more than 30 years of operation, it is evaluated the parameters of seismic response according to the seismic hazard regulations that appear during the useful life of the structure, these being: the Ecuadorian Code of Construction of 1977 (CEC-77), the Ecuadorian code of construction 2000 (CEC-2000) and the NEC-15. The analysis is executed from the structural modeling in software of structural analysis, which is the key point to execute a correct analysis, this model must represent the most significant characteristics of mass, rigidity and geometric configuration of the building under study. The gravitational loads in the building are evaluated and the vibration period of the structure is obtained from a modal analysis, which gives an indication of the behavior of the structure by its geometric characteristics and its own weight. In the core of the work the seismic response is evaluated from static and dynamic linear analysis proposed by the local standard, which includes the obtaining of shear at the base of the structure, and the basal shear coefficient, which allows the creation of the design inelastic response spectra for a return period of 475 years, and compliance with maximum drifts is verified. The results obtained with the NEC-15 for the static and dynamic linear analysis are compared with those resulting from the application of the CEC-77 and CEC-2000 regulations, considering that there is variation in the requirements used, and in the considerations themselves for obtaining the design spectrum. Next, the performance level of the structure for a very rare earthquake, with a return period of 2500 years is verified, the results are obtained from the static non-linear analysis (Pushover). Finally, the results of basal shear, inelastic spectra and maximum drift compliance are presented, as well as the level of structural performance reflected in the respective conclusions.